Period Poverty Beyond Hygiene: Intersectional and Feminist Public Health Research Perspectives : Period Poverty: Intersectional Public Health Perspectives - Zakki, Shahbaz Ahmed; Tahir, Majid Ali (Pakistan Journal of Health Sciences, 2026)
Period poverty is often discussed as a matter of hygiene. Sometimes it is framed as a problem of access to sanitary products. Yet such descriptions are too narrow for what has become one of the clearest expressions of gendered public health inequality in low- and middle-income countries (LMICs) [1]. Period poverty is not simply about pads, cloths, medications, or menstrual cups. It reflects the unequal social organization of health, dignity, mobility, education, and power. It is a structural, social, political, and public health phenomenon, deeply relational [2]. Menstruation health remained hidden within policy and research spaces. Period health remained invisible in mainstream public health discourse for decades. Conditions that affect millions of menstruating individuals across schools, workplaces, prisons, refugee camps, and households were treated as private discomforts rather than collective policy failures [3]. This absence was never neutral, which reflected longstanding patriarchal assumptions about whose bodies matter in health systems and whose suffering remains socially acceptable. Research from LMICs consistently documents stigma, shame, taboos, and social isolation associated with menstruation. Girls miss school because they cannot afford sanitary materials or because schools lack WASH, including water, safe toilets and waste management facilities. Women improvise with unsafe materials, due to which some remain isolated during menstruation, whereas others continue to work in unsafe and unhygienic environments because missing a day's wage is also not a good option to choose for them [4]. These experiences are not isolated incidents, but they represent patterned inequalities that public health systems can measure, observe, and prevent. Manifestation of period poverty is relational and intersectional [5]. Menstruation itself may be biological, but menstrual disadvantage is socially produced. A girl studying in an urban private school with functioning toilets, disposal systems, water access, and family support experiences menstruation differently from a rural adolescent within the same country, supposed to be Pakistan, attending a school without support and sanitation facilities. A refugee adolescent faces different vulnerabilities than a university student. A menstruating person living with disability experiences barriers differently from others [2, 6]. These differences matter because period poverty is shaped through the interaction of gender with class, geography, disability, displacement, education, and social exclusion [7]. Period poverty is a measurable structural deprivation with identifiable biological, social, economic, institutional, and political determinants [8]. Research studies should map multidimensional indicators, including school and workplace absenteeism, menstrual stigma, psychosocial distress, WASH access, product affordability, disposal facilities, and mobility restrictions. Furthermore, participation barriers, reproductive infections, policy exclusion, gender norms, decision-making autonomy, safety concerns, productivity loss, and social isolation would also be considered to better understand its ontological and intersectional realities [9, 10]. This ongoing lack of visibility of period poverty is symptomatic of women's and marginalized communities' wider experience of structural inequality affecting them drastically. Thus, a critical and emancipatory public health strategy must go beyond the measurement of rates of prevalence. It requires interrogation of systems that normalize menstrual inequity. Menstrual taxation, as a treatment of essential products, rather than a luxury, underscores inequities in governance and economic policy. The understanding of menstrual inequity can only happen through an informed conversation [11]. Valid knowledge and facts in the field of public health must be backed up with quantitative evidence, as well as lived experiences. For the future of progress, political commitment and institutional recognition of the importance of menstrual health as not being a peripheral development issue will be required in LMICs. Instead, it is at the heart of education, gender equality, employment, social inclusion, and psychosocial well-being. Public health could not claim commitment to equity while menstrual needs remain neglected across societies, households, schools, workplaces, health systems, and humanitarian settings. Period poverty is not only a women's issue but a public health concern that has social and economic intergenerational implications. It requires more than awareness slogans to discuss this very important matter. It calls for structural action based on dignity, equity, empowerment, and justice. Addressing the menstrual situation in LMICs is no longer about 'better management' of menstruation, but about challenging unequal structures that persist in excluding, silencing, and disadvantaging millions of people from the function of menstruation. Women need to be supported inclusively so that they can be empowered socially, legally, morally, and economically.